Natural Convection in a Square Cavity in the Presence of Heated Plate - Kandaswamy, P.; Lee, J.; Abdul Hakeem, A. K. K. (Nonlinear Analysis: Modelling and Control, 2007)
Natural convection heat transfer in a square cavity induced by heated plate is studied numerically. Top and bottom of the cavity are adiabatic, the two vertical walls of the cavity have constant temperature lower than the plate’s temperature. The flow is assumed to be two-dimensional. The discretized equations were solved by finite difference method using Alternating Direction Implicit technique and Successive OverRelaxation method. The study was performed for different values of Grashof number ranging from 103 to 105 for different aspect ratios and position of heated plate. Air was chosen as a working fluid (Pr = 0.71). The effect of the position and aspect ratio of heated plate on heat transfer and flow were addressed. With increase of Gr heat transfer rate increased in both vertical and horizontal position of the plate. When aspect ratio of heated thin plate is decreased the heat transfer also decreases. For the vertical situation of thin plate heat transfer becomes more enhanced than for horizontal situation.